A Robust Design approach for error reduction in Thermoelastic Stress Analysis on Ti6Al4V alloy in presence of unknow biaxial residual stresses - F. Di Carolo; U. Galietti (Heliyon)
In this study, a general model for Thermoelastic Stress Analysis (TSA) was employed in conjunction with simulated random noise sources to evaluate errors in the experimental technique using a robust design approach as a preliminary analysis. This facilitated the identification of an optimal experimental setup and anticipated ranges of measurement errors for TSA reducing testing time and errors. The model's validity was confirmed through TSA experiments conducted on AA2024 samples exhibiting biaxial residual stresses, as measured by a standard testing method. ANOVA (Analysis of Variance) and ANOM (Analysis of Means) analyses were conducted to explore the impact of parameters describing the analytical relationship between thermoelastic response and stresses in the presence of noise factors. The Robust Design approach was applied to the TSA measurement methodology, involving simulations of various noise sources and potential errors in the process, along with the application of different calibration methods.